Pemberdayaan Mahasiswa Melalui Webinar Inner Child untuk Meningkatkan Kesadaran Emosional dan Spiritualitas Islam - Siti Saodah Susanti; Laila Maharani (NuCSJo : Nusantara Community Service Journal, 2025)
The Community Service Program (PKM) aims to enhance students' psychological literacy and emotional awareness through a webinar themed "Women and Inner Wounds: Understanding the Inner Child and the Healing Process." The activity was conducted online on October 31, 2025, as a result of a collaboration between STAI Yamisa Bandung and UIN Raden Intan Lampung, with the active involvement of the Lentera Miya Student Activity Unit (UKM). The implementation method utilized a participative-educative approach through material presentation, interactive discussions, and guided self-reflection. A total of 40 students from the Islamic Education (PAI) and Islamic Family Law (HES) study programs actively participated. The evaluation results showed an increase in participants' conceptual understanding and reflective awareness: 86% of participants reported newly comprehending the inner child concept comprehensively, 78% were able to connect childhood experiences to their current emotional state, and 92% felt that the integration of Islamic values significantly aided the process of reflection and inner healing. The cross-campus collaboration proved effective in expanding the educational impact and enhancing students' capacity to understand mental health holistically. This activity demonstrates that collaborative-based educational intervention and the integration of Islamic spiritual values can serve as a model for student empowerment in the field of mental health